Exploring the influence of national music lessons on subjective well-being, self-esteem, and national identity among university students: a case study from China - Fu, Hongyu; Tu, Jinmei (Frontiers in Psychology, 2023)
This study aims to explore the influence of national music lessons on university students’ subjective well-being, self-esteem, and national identity. A Chinese university provided four national music courses spanning eight weeks. The students’ subjective well-being, self-esteem, and national identity were measured before the commencement of the courses (T1), the fourth week of the courses (T2), and post the completion of the courses (T3). A total of 362 participants completed the Positive and Negative Affect Scales, the Satisfaction with Life Scale, the Rosenberg Self-Esteem Scale, and the National Identity Scale at T1, T2, and T3. Results indicated that national music lessons could improve university students’ subjective well-being, yet there was no effect on their national identity or self-esteem. Although high national identity and high self-esteem predicted a greater level of subjective well-being, self-esteem and national identity didn’t affect the influence of national music lessons on subjective well-being. National music lessons were particularly beneficial to students with low and middle levels of subjective well-being, in comparison to those with higher levels of subjective well-being. This paper verifies an efficient method to bolster students’ subjective well-being that can be conducted in educational practices.